Selenium Vacancy–Enhanced Gas Adsorption of Monolayer Hafnium Diselenide (HfSe2) from a Theoretical Perspective. Issue 7 (29th April 2019) - Yang, Guofeng; Yan, Pengfei; Zhu, Chun; Gu, Yan; Lu, Naiyan; Xue, Junjun; Zhang, Xiumei; Sun, Rui; Fang, Xiudong
Abstract: The gas adsorption properties of monolayer selenium vacancy–defective (VSe ) hafnium diselenide (HfSe2 ) compared with that of pure monolayer HfSe2 for CO, NO, NO2, SO2, CO2, H2 O, H2 S, and NH3 molecules are theoretically investigated using density functional theory (DFT) based on first‐principle calculations. The equilibrium distance, adsorption energy, charge transfer, and electron localization function of pure and Se vacancy–defective HfSe2 (VSe ‐HfSe2 ) monolayers with absorbed gases are systematically calculated. It is demonstrated that monolayer VSe ‐HfSe2 exhibits enhanced adsorption energy and charge transfer than that of pure HfSe2, and the band structures reveal that the adsorption of CO, NO, NO2, and SO2 molecules can significantly modify the electronic structure of VSe ‐HfSe2 monolayer. In addition, the atom projected density of states suggests the existence of orbital hybridization between the gas molecules, and VSe ‐HfSe2 is the primary cause of high charge transfer. The results demonstrate that selenium vacancy will effectively enhance the gas adsorption ability for HfSe2 monolayer, especially for CO, NO, NO2, and SO2 molecules. Abstract : The density functional theory based on first‐principle calculations is used to investigate the gas adsorption properties of monolayer selenium vacancy defective (VSe ) hafnium diselenide (HfSe2 ) compared with that of pure monolayer HfSe2 theoretically, and it is shown the crystal and band structures of pure monolayer HfSe2 and selenium vacancy defective HfSe2 .